CAN GUANXI REDUCE TURNOVER INTENTION? A REVIEW PAPER - Jen Ling Gan; Halimah Mohd Yusof (International Journal of Accounting, Finance and Business, 2019)
The issue of employees’ turnover is still one of the critical phenomena among employees in organizations, although thousands of researches have been conducted in the past century. Actual turnover could lead to negative consequences to organizations, such as decreased productivity and lacking of manpower. When organizations lost talented and good employees, the competitiveness of organizations will be drastically decreased. Surprisingly, it was found that there is an increasing frequency of turnover in Asian organizations, which is including Malaysia. Malaysia has been facing critical turnover in manufacturing sector. In order to reduce actual turnover, the management should focus on turnover intention. This is because reduced turnover intention could help in reducing actual turnover. Therefore, it is crucial to investigate the factors that could affect turnover intention. Based on Job Embeddedness Theory, it is believed that good guanxi (workplace relationship) can help in reducing turnover intention. Guanxi has been always researched in China contexts, limited studies were conducted in Malaysia context. Malaysia is known as one of the countries that is relationship-oriented, which is similar with China. Hence, there is a need to explore the relationship between guanxi and employees’ turnover intention. The past studies that investigated the relationship between guanxi and employees’ turnover intention are important for this review paper. This review writing involved the articles that are ranged from 2008 to 2018, which is a decade. From the past studies, it was found that the relationship between guanxi and employees’ turnover intention among employees is inconsistent. Some studies revealed significant relationship, while other studies claimed that there is non-significant relationship between the variables. The inconsistency of findings has caused ambiguity to the linkage between the variables. It is recommended that organizations should put attention on organizing social activities in order to improve the guanxi among the employees, which in turn reducing the turnover intention.